Language maintenance in Sumbawa: Domains in the virtual accessibility of Istana Dalam Loka - Nurina Azyyati; Sri Wahyuni, Novi; Rahayu, Ratih (Lililacs Journal, 2024)
This study examines the dynamics of language maintenance at Istana Dalam Loka, focusing on the role of various domains in both physical and virtual access to the site. Utilizing data from Google Search and Google Trends, the research analyzes the prevalence of different domains—tourism, historical and cultural, religious, entertainment, and educational—within the virtual landscape, and compares them to their physical reality. The findings indicate that tourism is the most dominant domain, both in physical and virtual contexts, followed by historical and cultural activities. However, despite the stream of external influences through tourism, the study reveals a strong resistance to language and cultural differences, as the local Sumbawa culture remains deeply rooted in activities conducted at Istana Dalam Loka. This cultural resistance suggests that Sumbawa language and cultures are being maintained through a process similar to a sociolinguistic diversity of 'melting pot,' where diverse languages and cultures are integrated to the Sumbawa language and culture. The study concludes that while virtual access offers an alternative platform for language contact and multicultural engagement, it is primarily locals who both produce and consume content related to Istana Dalam Loka in virtual access. It also ensures the continued dominance of Sumbawa language and culture.